PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN LITERASI BAHASA INDONESIA SISWA KELAS I SEKOLAH DASAR - Latifah, Nur; Sa’odah, Sa’odah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This research is to determine the effect of student’s literacy abilities in Indonesian Language Lessons between students who are given a contextual approach with students who are given conventional teaching. This research uses quasi experimental methodology, subject population in this study were all students of class I SDN Babakan Asem 2 Kabupaten Tangerang consisting of 41 students. IA class consisting of 21 students as the experimental class and IB class consisting of 20 students as the control group. Data collection techniques in this study used test instruments. The results of this study are that there is a significant influence on the contextual approach to the literacy ability of Indonesian Subject in class I SDN Babakan Asem 2 Kabupaten Tangerang. This is evidenced in the results of hypothesis testing conducted in two different classes. The results obtained at posttest by hitting= 8, 74 > table= 2, 02.